Methotrexate-associated primary hepatic malignant lymphoma following hepatectomy: A case report. (2017) - Takei, Daisuke; Abe, Tomoyuki; Amano, Hironobu; Hirano, Naomichi; Kobayashi, Tsuyoshi; Ohdan, Hideki; Kondo, Toshinori; Nakahara, Masahiro; Noriyuki, Toshio
Highlights: Primary hepatic lymphoma is difficult to diagnose preoperatively. MTX use encouraged MTX-related ML. In MTX-related MLs, withdrawing MTX had a therapeutic effect. Abstract: Introduction: Recently, immunosuppressant-associated malignant lymphoma (ML) cases have been increasing along with the development of several effective immunosuppressant drugs for rheumatoid arthritis (RA). Among methotrexate (MTX)-associated lymphoproliferative disorders, primary hepatic lymphoma (PHL) in patients with RA following surgical resection has not been reported previously. Presentation of case: A 65-year-old woman who is a hepatitis B virus carrier with a history of RA was admitted. MTX was introduced seven years prior as an RA treatment. Her laboratory data showed no elevation of several tumor markers, and liver function test results were normal. On contrasted computed tomography (CT) scanning, a slightly enhanced tumor was detected at the early phase, and tumor staining was sustained at the delayed phase. Further, subsegmentectomy of the S6 was performed. The pathological diagnosis was diffuse large B-cell lymphoma. However, positron emission tomography-CT and bone marrow aspiration sample showed no resident sign of ML. Discussion: Diagnosis of PHL before surgery is difficult. If the mass lesion was solitary and had a certain degree of size, then resection could be performed for its treatment and diagnosis. The treatment for ML requires a diagnosis of the subtypes to select a therapeutic agent and determine the prognosis. Once a precise preoperative diagnosis was made, withdrawing MTX could be the first treatment in case of MTX-related ML. Conclusion: Long-term usage of immunosuppressant drugs could cause proliferative ML. Considering the increasing occurrence of MTX-related ML, withdrawing MTX should be considered, especially in patients with long-term immunosuppressant usage for RA.